Natural Semantic Metalanguage of Action Verbs in Balinese - Putu Candra Gunasari, Ni; Budiarsa, Made; Artawa, Ketut; Sri Satyawati, Made (International Journal of Psychosocial Rehabilitation, 2020)
The current article aims at explaining the components and semantic structure of event verbs in Balinese. In explaining the components and the semantic structure, this research applied the design of the Natural Semantic Metalanguage (NSM) approach, which is a semantic theory that uses the semantic primitive device proposed by Wierzbicka. The results of the research have described how the components as well as the semantic structure of event verbs in Balinese appeared.